2020
DOI: 10.1021/acs.organomet.0c00627
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Carbamoylphosphates from Isocyanates Catalyzed by Rare-Earth-Metal Alkyl Complexes with a Silicon-Linked Diarylamido Ligand

Abstract: Neutral rare-earth-metal monoalkyl complexes and anionic rare-earth-metal dialkyl complexes with a silicon-linked diarylamido ligand were synthesized and characterized, and their catalytic activities toward the additions of dialkyl phosphites to isocyanates were developed. Reactions of rare-earth-metal trialkyl complexes RE­(CH2SiMe3)3(THF)2 with a silicon-linked diarylamine ligand in n-hexane afforded the neutral rare-earth-metal monoalkyl complexes LRE­(CH2SiMe3)­(THF)2 (RE = Y (1), Er (2); L = (Me2Si)­(2,6-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…34 More typical approaches include acid-base reactions of the protonated form of a ligand, H 2 L (proligand), with the RE alkyls, 18 or metathesis reactions of alkali metal (A) salt A 2 [R 0 2 Si(NR) 2 ] with RE halides. 17,[21][22][23][35][36][37][38] Since a salt metathesis approach is the most common, we decided to probe it with potassium and lithium salts A 2 L. To deprotonate the starting proligands, KH and BuLi were used as bases. Deprotonation of H 2 L Dipp with BuLi proceeded fast in hexane or thf/hexane solutions.…”
Section: Synthesis and Structuresmentioning
confidence: 99%
See 2 more Smart Citations
“…34 More typical approaches include acid-base reactions of the protonated form of a ligand, H 2 L (proligand), with the RE alkyls, 18 or metathesis reactions of alkali metal (A) salt A 2 [R 0 2 Si(NR) 2 ] with RE halides. 17,[21][22][23][35][36][37][38] Since a salt metathesis approach is the most common, we decided to probe it with potassium and lithium salts A 2 L. To deprotonate the starting proligands, KH and BuLi were used as bases. Deprotonation of H 2 L Dipp with BuLi proceeded fast in hexane or thf/hexane solutions.…”
Section: Synthesis and Structuresmentioning
confidence: 99%
“…It has been recently demonstrated that such species derived from alkyl complexes [RE(L)(Alkyl)(thf) 2 ] can be used as effective catalysts of addition of isocyanates to dialkyl phosphites. 17 Similar complexes [RE(L)(N(SiMe 3 ) 2 )(thf)] (RE = Y, Nd, Sm, Eu, Yb; Aryl = Ph or 2,6-diisopropylphenyl (Dipp); R' = Me) exhibit high catalytic activity and selectivity in the cyclotrimerization of aromatic isocyanates and cyclodimerization of aliphatic isocyanates, 18 and those with macrocyclic anionic analogue [La{MeTACN(SiMe 2 )N t Bu}(CH 2 SiMe 3 )(m-CH 2 )] 2 (TACN = 1,4,7-triazacyclononane) are active in the dimerization of phenylacetylene. 19 Coordination of two ligands to the RE center would lead to anionic [RE(L) 2 ] À or ate-complexes [RE(L) 2 M] (M = alkali metals).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our group has synthesized different types of rare‐earth metal complexes bearing a silicon‐linked diarylamido ligand and employed them in several catalytic reactions, such as cyclotrimerization or cyclodimerization of isocyanates by the rare‐earth metal amides [(Me 2 Si)(2,6‐ i Pr 2 C 6 H 3 N) 2 ]REN(SiMe 3 ) 2 (THF) (RE=Yb, Y, Sm), [15] and the additions of dialkyl phosphites to various alkyl‐ and aryl‐substituted isocyanates by the rare‐earth metal alkyl complexes [(Me 2 Si)(2,6‐ i Pr 2 C 6 H 3 N) 2 ]RE(CH 2 SiMe 3 )(THF) 2 (RE=Y, Er) [16] . Based on our previous studies on the transformation of isocyanates, we believed that the rare‐earth metal complexes can catalyze the hydroamination of isocyanates in a similar process.…”
Section: Resultsmentioning
confidence: 99%
“…All manipulations of air‐ and moisture‐sensitive materials were performed under a dry argon atmosphere using standard Schlenk techniques or in a glovebox. Rare‐earth metal complexes [(Me 2 Si)(2,6‐ i Pr 2 C 6 H 3 N) 2 ]YN(SiMe 3 ) 2 (thf), [15] and [(Me 2 Si)(2,6‐ i Pr 2 C 6 H 3 N) 2 ]Y(CH 2 SiMe 3 )(thf) 2 [16] were prepared according to the literature method. Diphenylphosphine and amines were purchased from TCI and distilled prior to use.…”
Section: Methodsmentioning
confidence: 99%